2004
DOI: 10.1118/1.1739003
|View full text |Cite
|
Sign up to set email alerts
|

MRI/TRUS data fusion for prostate brachytherapy. Preliminary results

Abstract: (Received Prostate brachytherapy involves implanting radioactive seeds (I 125 for instance) permanently in the gland for the treatment of localized prostate cancers e.g. cT1c-T2a N0 M0 with good prognostic factors. Treatment planning and seed implanting are most often based on the intensive use of transrectal ultrasound (TRUS) imaging. This is not easy because prostate visualization is difficult in this imaging modality particularly as regards the apex of the gland and from an intra-and inter-observer variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 15 publications
1
69
0
2
Order By: Relevance
“…However, prostate dose constraints are still verified on MRI+US contours for those 8 patients. This has to be confirmed on a larger number of patients since some preliminary evaluation exhibited cases where the D90 was substantially lower than expected (see [6]). This has also to be confirmed on organs at risk but this requires software modification which is in progress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, prostate dose constraints are still verified on MRI+US contours for those 8 patients. This has to be confirmed on a larger number of patients since some preliminary evaluation exhibited cases where the D90 was substantially lower than expected (see [6]). This has also to be confirmed on organs at risk but this requires software modification which is in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Residual surface distance was measured for 11 patients; TRE was evaluated for only 4 of them who were equipped with an endourethral probe making the urethra fully visible on TRUS and MRI modalities. [6] for more details).…”
Section: Fig 2 Mri/trus Fusion For Brachytherapy: (Left) Two Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that the use of additional information from MR imaging can reduce inter-observer variability of prostate delineation in CT images or TRUS images and thus improve the treatment planning [20,6]. Moreover, new MR modalities such as MR spectroscopy (MRS), dynamic contrast enhanced MRI (DCE-MRI) with gadolinium injection or lymphotrophic nanoparticle enhanced MRI (LN-MRI) have emerged as new, promising methods for the detection of prostate cancer.…”
Section: Previous Workmentioning
confidence: 99%
“…11). Authors (74,75) have shown that fusing preoperative MR to intraoperative US can help to prevent underestimation of prostate volume, especially at the apex and base, with a positive impact on treatment planning.…”
Section: Mr-guided Trus For Prostate Brachytherapymentioning
confidence: 99%